Analysis Global of The Effect of Corporate Social Responsibility On Financial Performance - Putri, Shalsa Billa Eka; Wardani, Farah Arda; Hwihanus, Hwihanus (Indonesian Journal Publisher, 2024)
This study investigates the effect of CSR on corporate financial performance globally. Data is drawn from various countries to provide a broader picture. Meta analysis was used to collect data from various online sources mainly from Google Scholar. The research results from seven indexed international journals showed mixed findings. Some journals show a positive relationship between CSR and financial performance, while others highlight a negative impact, especially in the short term. Factors such as firm size, industry, and geographical location moderate the relationship. The discussion outlines the importance of CSR in a global context, relevant theories, and challenges in this research. In conclusion, firms are advised to integrate CSR in their various business strategies to improve financial performance, although it requires further research to confirm the causal relationship.